The effect of essential oils from the coriander and fennel fruits on the weight and hematological parameters of piglets during the rearing period - Volchenkov Yuri; Ostrenko Konstantin (BIO Web of Conferences)
The article presents data on the study of weight and hematological parameters of piglets in the post-weaning period against the background of the use of coriander and fennel essential oils. The physiological experiment was carried out on 15 crossbreed young hogs (F1:(D*L)) with an initial live weight of 11.95-12.56 kg at the age of 45 days. The duration of the experiment is 80 days. The inclusion of fennel and coriander essential oils in the diet made it possible to increase the average daily gain by 4.45-6.23%. Morphological parameters of blood increased in growing young animals: erythrocytes by 1.46-2.93%, hemoglobin by 7.86-8.71%.